2018
DOI: 10.1029/2018jc014054
|View full text |Cite
|
Sign up to set email alerts
|

A New Assessment of Mesoscale Eddies in the South China Sea: Surface Features, Three‐Dimensional Structures, and Thermohaline Transports

Abstract: By analyzing 22 years (1993By analyzing 22 years ( -2015 of daily eddy data, statistics of surface eddy properties were refreshed in the South China Sea. More than 7,000 of historical Argo profiles were collocated into eddy-centered coordinates to reveal the composite mean three-dimensional structure of eddies. The results indicate that eddies of both polarities have long conical shape, with a maximum (minimum) density anomaly of 0.55 kg/m 3 (À0.51 kg/m 3 ) at 60 m (90 m) in the composite cyclonic (anticycloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
81
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 76 publications
13
81
1
Order By: Relevance
“…Compared with the climatological result, the temperature shows an anomaly larger than 2.5°C at 100-200 m in the eddy center. The anomaly still reaches about 0.5°C at 600 m (Figure 3d), which is larger than the mean value of~0.1°C at 500 m for anticyclones in the SCS (Chen et al, 2011;He et al, 2018). This indicates that the WAE is vertically extending deeper than the mean shape of anticyclones in the SCS, consistent with the observation in 2004 (Figure 2).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Compared with the climatological result, the temperature shows an anomaly larger than 2.5°C at 100-200 m in the eddy center. The anomaly still reaches about 0.5°C at 600 m (Figure 3d), which is larger than the mean value of~0.1°C at 500 m for anticyclones in the SCS (Chen et al, 2011;He et al, 2018). This indicates that the WAE is vertically extending deeper than the mean shape of anticyclones in the SCS, consistent with the observation in 2004 (Figure 2).…”
Section: Resultssupporting
confidence: 81%
“…Mesoscale eddies are quite active in the South China Sea (SCS) (Chen et al, ; He et al, ; Hwang & Chen, ; Wang et al, ). They have profound effects on heat and salt transport (e.g., (Chen et al, )), chlorophyll distribution (e.g., (He et al, ; Liu et al, )), primary productivity (Lin et al, ), variation of sea surface temperature and wind (Chow & Liu, ), inertial energy propagation (Chen et al, ), and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoscale eddies are active in the NSCS due to wind stress curl (Qu, ; Wang, Chen, et al, ), Kuroshio current loops (Jia et al, ; Zu et al, ), and the intrusion of western Pacific water masses (Hu et al, ; Wu & Chiang, ). Previous studies have investigated the spatiotemporal distribution, properties, motions, and structures of mesoscale eddies in the NSCS (Chen et al, ; He et al, ; Lin, Dong, et al, ; Wang et al, ; Xiu et al, ; Xie et al, ; Zhang et al, ). Wang et al () grouped eddies in the SCS into four geographic zones and found that mesoscale eddies originated mainly in the regions southwest of Taiwan, northwest of Luzon Strait, and offshore of central Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…species composition (EDDIES) in the Sargasso Sea off Bermuda [5], meso-and submesoscale processes in an intense front (AlborEx) [6] and the northwestern Pacific eddies, internal waves and mixing Experiment (NPEIM) [7], and so forth. Nowadays, main observation methods for field experiment include Argo floats, moored instrumentation, underwater gliders and shipboard survey.Argo profiling floats, which are designed to measure underwater ocean temperature and salinity (T/S) [8], are one of the effective methods to obtain 3D mesoscale eddy structures [9][10][11][12][13]. However, due to the drift features, the detailed structure of a specific eddy is difficult to acquire unless a large number of Argo floats are deployed inside the targeted mesoscale eddy.…”
mentioning
confidence: 99%
“…Argo profiling floats, which are designed to measure underwater ocean temperature and salinity (T/S) [8], are one of the effective methods to obtain 3D mesoscale eddy structures [9][10][11][12][13]. However, due to the drift features, the detailed structure of a specific eddy is difficult to acquire unless a large number of Argo floats are deployed inside the targeted mesoscale eddy.…”
mentioning
confidence: 99%